Preparation and characterization of anti-corrosive coatings based on silane functionalized graphene oxide/ epoxy resin nanocomposites - Musa, Aujara Kabiru (2020)
Epoxy resins are generally used to protect metal substrates, however, there is a need for improvement of anti-rust performance and mechanical properties. The addition of nano-sized fillers such as graphene to produce nanocomposites can overcome the shortage of polymeric materials and has remarkable mechanical, electrical, and gas barrier properties. In this study, graphene oxide and functional-GO were incorporated into epoxy resins to provide a protective layer of the metal substrate. Functional-GO is synthesized using environmentally friendly gamma irradiation techniques, which are a simple and clean alternative approach to alter the structural and physicochemical properties of graphene oxide (GO). Graphene oxide obtained by Hummer method was modified by incorporating 3-Aminopropyltriethoxysilane (APTES) and 3-Glycidyloxypropyltrimethoxy silane (GPTMS) to its surface by radiation from gamma ray. The nature of GO and functional-GO is characterized by various techniques such as Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction spectroscopy (XRD), field release scanning electron microscope (FESEM), Raman spectroscopy, and thermogravimetric analysis (TGA). The FT-IR spectrum reveals chemical interactions between the cross section which shows significant weakening of the -OH, COOH and C-O-C with the appearance of chemical bonds due to the withdrawal of oxygen functional groups on the GO surface where crystal surface changes and surface defects due to modification are determined by XRD which shows the gradual weakening with simultaneous disappearance of graphite peak as the oxidation process proceeds with the corresponding appearance of diffraction peak at about 2θ=9.8 leading to an increased in the interlayer spacing from 0.34nm to 0.90nm. Similarly, the Raman spectroscopy indicate an increase in ID/IG from 0.90 for GO to 1.21 and 1.18 for AGO-150 and GGO-150 respectively. The TGA thermograms showed peaks at various temperature regions (i.e. 30-120°C, 120-300°C and 300-650°C) which can be attributed to the degradation oxygen functional groups and chemically bonded silane on the GO surface. Within these temperature regions the AGO-150 exhibits highest thermal stability with the lowest water evaporation (5.5%), lowest decomposition of unreacted silanes (9.36%) and thermal-oxidative decomposition of grafted silane (32.17%). Preparation of the protective material of the steel substrate begins by ultrasonically dispersing the 1 wt.% GO in the solvent before mixing it by shearing it into an epoxy matrix and adding a hardener. XRD showed the existence of GO morphology, functional-GO intercalation and exfoliation throughout the matrix shown by the existence of broad diffraction peak of epoxy between 2θ=5-28° centered at 2θ=18° indicating the dispersion of functionalized-GO in the matrix. SEM on the sample surface layer determined during the tensile test showed microscopic and homogeneous functional-GO dispersion in the matrix. Thermogravimetric analysis (TGA) through the analysis of some thermodynamic parameters such as Ton, W350°C, Tmax and T500°C all revealed improved thermal stabilities of nanocomposites coatings fabricated with functionalized-GO. The dynamic mechanical analysis (DMA) was used to investigate the thermomechanical properties of nanocomposite coatings. Thermodynamic parameters such E’ and Tg of the nanocomposites coatings showed a significant increase in storage modulus and a gradual increase in glass transition temperature with the dispersion of functionalized-GO, where EAG-150 exhibits highest E’ of 3414.90 MPa and Tg of 90.49°C. The physical properties of coatings such as adhesion, hardness, flexibility, and chemical properties are also assessed. Corrosion resistance of nanocomposite layers in NaCl solution (3.5% by mass) was also assessed using Open Circuit Potential (OCP), potentiodynamic polarization, and Electrochemical Impedance Spectroscopy (EIS). The results showed that the functional nanocomposite layer-GO is capable to block the penetration of electrolytes between the metal surface and the coating. This study shows that Functional-GO /epoxy nanocomposites provide better corrosion protection and can act as an excellent corrosion barrier on lightweight steel substrates due to improvement of some electrochemical properties such as shifting of Ecorr to more positive value i.e., from -0.853554V for EP to -0.18488 for EAG-150 and decreasing of Icorr value from 8.349×10-7 for EP to 5.281×10-8 for EAG-150. This improvement in corrosion protection behavior can be attributed to the GO two-dimensional (2D) structure and outstanding performance, which can hinder the penetration of corrosive media to a certain extent, thereby enhancing the anti-corrosion properties of the coatings.